STUDI LITERATUR: POPULARITAS DAN TINGKAT KEBERHASILAN ACTIVITY-BASED COSTING DI BERBAGAI NEGARA - Siahaan, Johan; Br. Tobing, Gresi Lusina; Dolok Saribu, Ardin; Hutahaean, Marlia Olivia; Sembiring, Anisa Putri; Silaban, Ester; Miranda, Elsa; Simanjuntak, Evelyn (LPPM Universitas Putera Batam, 2024)
This study aims to determine the popularity of Activity-Based Costing (ABC) methods and the success rates of countries adopting the ABC system. The research method used is a literature review. The main journal was used as a basis for comparison. The abstract is